Effective instruction for STEM disciplines : from learning theory to college teaching - Mastascusa, E. J.; Snyder, William J. ;Hoyt, Brian S. (San Francisco, California : Jossey-Bass Inc., Publishers, 2011)
This book offers information on the most effective ways that students process material, store it in their long-term memories, and how that effects learning for long-term retention. It reveals how achieving different levels is important for "transfer" which refers to the learner's ability to use what is learned in different situations and to problems that might not be directly related to the problems used to help the student learn. Filled with tools, techniques, and approaches, this book explores how to apply these approaches to improve teaching.
1. Is there a problem? : Or is the problem that we don't think there is a problem? -- 2. Learning and memory: how does learning happen? -- 3. Perception: when all else fails, start at the beginning -- 4. Processing and active learning: how does it happen? -- 5. Bloom's taxonomy of educational objectives: its relationship to course outcomes -- 6. Interactive engagement and active learning: retrieval events -- 7. Some active learning techniques: studying, retrieval, and schemata construction -- 8. Problem-based learning: where am I ever going to use this stuff? -- 9. Transfer: what are your course outcomes? -- 10. Teaching for transfer: applying what is known -- 11. Applications.
Includes bibliographical references and index.
Keywords: COLLEGE TEACHING